(untitled) (University of Khartoum Engineering Journal, 2022)
Aerial and satellite images are conventionally used as a main data source for image-based geospatial data collection, map production, and updating purposes. However, it can be time consuming and costly to obtain them. Recently, Unmanned Aerial Vehicles (UAVs) are emerging as suitable technology, which has the potential to provide information with a very high spatial and temporal resolution at a low cost. This paper aims to demonstrate and evaluate the potential of using UAVs for 3D photogrammetric mapping and GIS development as an affordable solution for many developing countries. Part of Khartoum railway station is used as a case study in which 127 images were collected with a DJI Phantom 4 at a flying height of 100 m. RTK-GPS and ground control points are used to improve the absolute accuracy of dereferencing. Two different software, namely, Pix4D and Photo scan are used to generate standard geospatial products such as Digital Surface Model (DSM), Digital Terrain Model (DTM), and orthophoto covering 0.225 km² with a spatial resolution of 3.61 cm. The final orthophoto with a positional accuracy of 2.4 cm was used to extract features for mapping purposes. General quantitative and qualitative control of the UAV data products and the final outputs were performed, indicating that the obtained accuracies comply with international standards. Moreover, possible problems and further perspectives were also discussed. The obtained results demonstrate that UAVs provide promising opportunities to create high-resolution and highly accurate orthophotos, thus facilitating map creation and updating. In addition, it demonstrates the capability of commercial photogrammetric software packages for automatic 3D reconstruction.